PERLINDUNGAN TERHADAP PENONTON FILM (Analisis Isi UU No. 33 Tahun 2009 tentang Perfilman) - , Itsna Hidayatul Khusna; , Dr.phil.Ana nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the reason why communication policies made is that people survived in the communication process. The law is a form of policy. Legislation made based on Pancasila, and material contents must not different with the UUD 1945 and human rights. One of the communication policy in Indonesia is UU No. 33 Tahun 2009 tentang Perfilman. Film Law is a policy that governs all things related to the film industry in Indonesia, one of which contains the rules of society. Society is positioned as audiences and consumers have the right basic consumer rights that are universally recognized. This research seeks to look at the protection film audiences based on consumers' rights are taken from the Universal Declaration of Human Rights (UDHR) and the Consumer Protection Act. To look at the issue protection film audiences in the Film Act, researcher used qualitative content analysis as the method. Content analysis is a method used to view the contents of a statute to determine the characteristics of a statute . Contained 90 subsection of UU No. 33 Tahun2009 tentang Perfilman . After doing the analysis , based on the above consumer rights , the protection obtained by movie audiences based on UU No. 33 Tahun 2009 tentang Perfilman is : they are safe in their actions in this communicating safely while he was in a movie performances spaces , there is a notice that the film will be watched by an audience age classification of films , there is a passing mark sensor for the film to be screened , get clarity of the ad/reclame films , ad/reclame film made for must not different with the contents of the film to be screened , the presence of LSF , the regulator in charge of film censorship film to be screened , receive education by LSF on age classification sensors and films , and the means of obtaining ease infrastructure performance films .